Power-Law Online Terrorism and Extremism - Baele, Stéphane J. (Perspectives on terrorism, 2025)
This Research Note draws attention to the ubiquity of heavy-tailed, power-law types of data distribution in all major dimensions of digital extremism and terrorism, and discusses the important implications stemming from this pattern as well as the mechanisms underpinning it. Highly unequal distributions with a very long lower tail and a sharply rising upper tail indeed characterize linguistic content, individual behaviours, and overarching structures of extremist/terrorist digital ecosystems ? a striking feature that has largely escaped terrorism and extremism scholars? scrutiny as well as Counter Violent Extremism (CVE) and Counter-Terrorism (CT) practitioners, despite its scientific and practical significance.